Inactivation and Heat Stabilization of Poliovirus by 2-Thiouracil - Steele, Frances M. (1967)
Treatment of poliovirus Type I with 10(−3)m 2-thiouracil (2-TU) resulted in the inactivation of greater than 90% of the virus infectivity and stabilization of approximately 50% of the residual virus to heat inactivation. These effects were due to a reaction with the protein moiety of the virus and could be blocked by pre-treatment of the virus with l-cystine or of the drug with cysteine. Both inactivation and stabilization occurred synchronously and reached equilibrium at the same time. Neither process was reversed by reducing agents. It is suggested that an oxidized form of 2-TU reacts with capsid sulfhydryl groups to form a product which is stable in either the inactive or heat-resistant form.